Development of an Authentic Assessment Model in Mathematics Learning: A Science, Technology, Engineering, and Mathematics (STEM) Approach - I Wayan Widana; Agus Tatang Sopandi; Gede Suwardika (Universitas Jambi, Indonesia, 2021)
STEM (Science, Technology, Engineering, Mathematics) approach in mathematics learning is very suitable for improving higher-order thinking skills. However, the ability of teachers to develop authentic assessment models based on the STEM approach is still low. This study aims to develop an authentic assessment model suitable for learning based on the STEM approach in mathematics at Senior High School. This study used a Research & Development design adapted from the Borg & Gall model. Data were collected using a validation sheet and a questionnaire. The data source was 269 teacher respondents selected using multistage random sampling technique, while two experts from higher education as validators and 21 senior high school math teachers experienced as panellists were determined by purposive sampling technique. Data were analysed through a quantitative approach. The product of this research is an authentic assessment model consisting of twenty project tasks. The results of the analysis show that 16 project tasks with very good quality and four project tasks with good quality, declared appropriate and in accordance with the STEM approach-based learning.